ACUTE EPIGLOTTITIS IN CHILDREN (ETIOPATHOGENESIS, DIAGNOSIS, TREATMENT) - M.S. Savenkova; G.L. Balyasinskaya; V.A. Bychkov; G.M. Voronyuk; L.M. Korobko; A.N. Anin ("Paediatrician" Publishers LLC, 2008)
Acute epiglottitis (AE) must be considered as not a separate entdisease but as compound pathology with wide polymorphism, which can often need an intervention of different medical specialists: experts in resuscitation, infectiologists, immunologists, pulmonologists, and cardiologists. The increase of rate of AE and its septic complications and severe outcomes in last years forced us to consider this problem in detail on the basis of longstanding experience of Morozov children's city clinical hospital. Key words: children, acute epiglottitis, etiology, diagnosis, treatment.